Real-life data of direct anticoagulant use, bleeding risk and venous thromboembolism recurrence in chronic thromboembolic pulmonary hypertension patients: an observational retrospective study - KOCAKAYA, DERYA (SAGE PUBLICATIONS INC, 2020)
Introduction Lifelong anticoagulation is the cornerstone of the chronic thromboembolic pulmonary hypertension (CTEPH) treatment regardless of the additional pulmonary endarterectomy, balloon pulmonary angioplasty, or medical treatment alone. Aim of this study was to evaluate the rate of oral anticoagulant preferences and document direct oral anticoagulants' (DOACs') safety, efficacy in the CTEPH population. Methods Patients' demographic data obtained from database between September 2011 and April 2018. In-hospital events, death, venous thromboembolism (VTE) recurrence, bleeding events and anticoagulant therapy transition were recorded. Results We reviewed 501 CTEPH patients who observed 9.0 +/- 8.5 years. All-cause death, all bleeding, recurrent VTE was observed in 15.6%, 31% and 12%. Forty-one patients (8.2%) were diagnosed as inoperable. Of all, 15.2% of operable patients remained as residual. All-cause mortality rates were 13.8% (57 pts.) in the warfarin group as compared with 9.7% (13 pts.) in rivaroxaban group (HR: 1.61, 95% CI, 0.89-2.99; p: 0.11). Higher bleeding events occurred with warfarin group (27.1%) as compared with rivaroxaban (24.6%; HR: 1.28, 95% CI, 0.86-1.88; p: 0.22). Major bleeding was significantly higher with warfarin group (HR: 1.94, 95% CI, 1.05-3.62; p: 0.03). Subgroup analysis of all-cause death revealed that this significance dominated by the rate of death according to bleeding events; warfarin versus those seen with rivaroxaban (4.85% vs. 2.2%; HR: 4.75, 95% CI: 1.12-20.16; p = 0.03). The rate of recurrent VTE was found 8.9% in the rivaroxaban group, 10.9% in warfarin group (HR: 1.21, 95% CI, 0.64-2.23; p: 0.55). Conclusion DOACs could be a safe and effective alternative for lifelong anticoagulant therapy in CTEPH patients. Rivaroxaban produced similar rates of thromboembolism and non-relevant bleeding compared to those associated with warfarin. The main difference was found with major bleeding that it was mainly associated with the death rate according to major bleeding. Using DOACs might be a more reasonable way to prevent bleeding events without increasing thromboembolic risk.
Keywords: chronic thromboembolic pulmonary hypertension; direct oral anticoagulant; warfarin; haemorrhage; thromboembolism; ENDARTERECTOMY; WARFARIN